Biomass distribution and allocation in diploid potato varieties (Solanum phureja Juz. et Buk.) - Tatiana M. Saldaña V. (Agronomía Colombiana, 2015)
It is necessary to study the photosynthate distribution pattern and allocation in Guaneña and Latina potato varieties, which come from the Colombia variety and are relatively new in agriculture, for potato crops in Colombia. The aim of this study was to determine the  distribution behavior of dry matter among the organs that make up the potato plant in order to determine the key moments in the crop cycle, where the filling of the tubers takes place, and to establish the pattern of biomass distribution in these varieties. Three consecutive experiments were performed at the “Estación Agraria Paysandú” in Santa Elena (Medellin- Antioquia), at 2,538 m a.s.l. with average temperatures of 13.6, 14.6 and 13.81ºC. The field trials were established under a random complete blocks design with a 3x2 factorial layout  and five replications. The first factor corresponded to the potato varieties and the second factor corresponded to the two fertilization levels: 7 and 21 g of fertilizer per planting site, representing 259.25 and 777.77 kg of fertilizer per ha. The higher fertilizer dose is  the one normally used by farmers. An NPK fertilizer compound (10 - 20 - 20 - 5(S)) was used. There were 30 experiment units with an area of 18.27 m2 (seven 2.7 m furrows  separated by 0.90 m); the distance between the plants was 0.30 m, for a density of 37,037 planting sites per ha. Weekly samplings were taken, a whole plant per experiment unit. The direct measuring evaluated variables for the dry weights of each organ, which were used to obtain curves and the distribution pattern. The development time was evaluated in accumulated growing degree-days and threshold temperatures of 2 and 29°C were used. In all of the varieties and the two fertilization treatments, most of the assimilates in the early stages of the cycle were concentrated in the roots, leaves and stems; once the tuber formation started, the leaves and stems started to allocate dry matter towards the filling of the accumulation organs.